Peranan etika dalam pelaporan maklumat alam sekitar di Malaysia - Romlah Jaffar,; Mohamat Sabri Hassan,; Nurisyal Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This study investigates whether users and preparers of environmental information have differing opinion in the importance of environmental information that caused the existence of information gap, meaning the information prepared fail to fulfill the information need of users. This study also examines whether the difference is due to the different ethical value between users and preparers of information. The legitimacy theory has been utilised to explain the information gap and the ethical ideology has been used to explain the individual ethical issue. Data was collected using research questionnaire that was sent to both preparers and users of environmental information. The results indicate that there is significant difference between users’ and prepares’ opinion on the importance of environmental information. The results also indicate that the ethical level of preparers and users are significantly different. Therefore, we conclude that the the difference in the ethical level between users and preparares of information has contributed to the environmental information gap between them. This finding provides an insight of the environmental disclosure practice in Malaysia